CHILDREN’S MENU OF HOSPITALITY INDUSTRY INSTITUTIONS: WAYS OF EXPANDING THE RANGE OF FISH DISHES - Дітріх, Ірина; Штома, Євген (SWorldJournal, 2023)
The presented work proves the feasibility of improving the traditional amateur fish cutlet recipe by completely replacing the main fish raw material with cod fillets with the addition of carrot purée and completely replacing auxiliary raw materials with r